2024
DOI: 10.1038/s41531-024-00677-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in PRKN-associated Parkinson’s disease

Poornima Jayadev Menon,
Sara Sambin,
Baptiste Criniere-Boizet
et al.

Abstract: Bi-allelic pathogenic variants in PRKN are the most common cause of autosomal recessive Parkinson’s disease (PD). 647 patients with PRKN-PD were included in this international study. The pathogenic variants present were characterised and investigated for their effect on phenotype. Clinical features and progression of PRKN-PD was also assessed. Among 133 variants in index cases (n = 582), there were 58 (43.6%) structural variants, 34 (25.6%) missense, 20 (15%) frameshift, 10 splice site (7.5%%), 9 (6.8%) nonsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 55 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Deletions of exon 3 and exon 3-4 of PRKN are the most frequent exon rearrangements reported, suggesting recurrent event in intron 2. 20,21 First, the size of intron 2 is equivalent to that of introns 4, 6, 7, 9 and shorter than intron 1, thereby excluding the hypothesis of a higher frequency due to a size effect. In addition, Mitsui et al showed that only a minority of breakpoints are recurrent and that various underlying mechanisms are implied in PRKN rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of exon 3 and exon 3-4 of PRKN are the most frequent exon rearrangements reported, suggesting recurrent event in intron 2. 20,21 First, the size of intron 2 is equivalent to that of introns 4, 6, 7, 9 and shorter than intron 1, thereby excluding the hypothesis of a higher frequency due to a size effect. In addition, Mitsui et al showed that only a minority of breakpoints are recurrent and that various underlying mechanisms are implied in PRKN rearrangements.…”
Section: Discussionmentioning
confidence: 99%